Difficulties of motion-onset VEP interpretation in school-age children - Kubova, Zuzana; Kuba, Miroslav; Kremlacek, Jan; Langrova, Jana; Szanyi, Jana; Vit, Frantisek; Chutna, Marie (Documenta ophthalmologica. Advances in ophthalmology, 2014)
BACKGROUND: In adults, motion-onset visual evoked potentials (M-VEPs) with a dominant N2 peak represent a useful diagnostic tool. However, it is difficult to use this type of VEP in children because of the long maturation (up to 18 years) of M-VEPs, which is characterised by a gradual decrease in N2 peak latency and shape development. Moreover, in some children, M-VEPs are difficult to identify with standard stimuli. METHODS: We tested features of M-VEPs in 30 children (7-12 years) with the following set of standard stimuli used in our lab for examining adults ( https://web.lfhk.cuni.cz/elf ): low-contrast translation motion (TM) and expansion/contraction motion (ExCoM) in full field and in periphery (with central 20° masked). In 16 children, a high-contrast TM was also tested. RESULTS: With standard (low-contrast) stimuli, a common M-VEP to TM and to ExCoM was detected in 77 and 83 % of children, respectively. The M-VEPs to ExCoM in the periphery were detected in only 43 % of children. An abnormal dominant P1 peak was found in 9 % of VEPs to TM, 12 % of VEPs to full-field ExCoM and 14 % of VEPs to peripheral ExCoM. The M-VEPs to all low-contrast stimuli displayed large inter-individual latency variability (N2 peak latency differed for more than 100 ms). High contrast (more suitable for the non-mature magnocellular pathway) shortened M-VEP latencies and improved amplitudes. CONCLUSIONS: Our findings show that the maturation of motion perception in children is inter-individually variable, which limits the diagnostic use of M-VEPs.
Keywords: Motion Perception; senzorické prahy; lidé; mužské pohlaví; dítě; Child; zrakové korové centrum; ženské pohlaví; Humans; vnímání pohybu; citlivost na kontrast; Contrast Sensitivity; Eye; Evoked Potentials, Visual; oči; Visual Cortex; Female; zrakové evokované potenciály; Sensory Thresholds; Male